Boosting the capacity of all-organic paper supercapacitors using wood derivatives. Issue 1 (5th December 2017) - Edberg, Jesper; Inganäs, Olle; Engquist, Isak; Berggren, Magnus
Abstract : The performance of an all-organic paper supercapacitor based on nanocellulose and a conductive polymer was greatly enhanced by incorporating lignin. Abstract : Printed and flexible organic electronics is a steadily expanding field of research and applications. One of the most attractive features of this technology is the possibility of large area and high throughput production to form low-cost electronics on different flexible substrates. With an increasing demand for sustainable energy production, low-cost and large volume technologies to store high-quality energy become equally important. These devices should be environmentally friendly with respect to their entire life cycle. Supercapacitors and batteries based on paper hold great promise for such applications due to the low cost and abundance of cellulose and other forest-derived components. We report a thick-film paper-supercapacitor system based on cellulose nanofibrils, the mixed ion-electron conducting polymer PEDOT:PSS and sulfonated lignin. We demonstrate that the introduction of sulfonated lignin into the cellulose-conducting polymer system increases the specific capacitance from 110 to 230 F g −1 and the areal capacitance from 160 mF cm −2 to 1 F cm −2 . By introducing lignosulfonate also into the electrolyte solution, equilibrium, with respect to the concentration of the redox molecule, was established between the electrode and the electrolyte, thus allowing us to perform beyond 700 charge/discharge cycles with no observed decrease in performance.